ANALISA PARAMETER OSEANOGRAFI UNTUK PENGEMBANGAN WISATA PANTAI PULAU GILI IYANG KABUPATEN SUMENEP - Fahmi Yudha Pratama; Agus Romadhon (Juvenil, 2020)
ABSTRACTGili Iyang Island is an area with potential and can be utilized that can attract domestic tourists and international tourists. One tourist area that can be an attraction is beach tourism. The development of a good coastal tourism area can have a positive impact on the people of Gili Iyang Island. To develop this potential, an analysis of the suitability of coastal tourism is needed. So that this study aims to determine the condition of oceanographic parameters for the development of coastal tourism. This study analyzes water quality including temperature, salinity, DO and pH, while coastal tourism suitability analysis includes beach type, current velocity, depth, beach width, water base material, slope, brightness, watershed cover, dangerous biota and freshwater availability. Based on the results of research on the quality of the waters on Gili Iyang Island, Sumenep Regency is in accordance with the standard quality standards for the development of coastal tourism. Based on the calculation of the Gili Iyang Island beach tourism suitability matrix, it has an appropriate rating (S) for the development of coastal tourism. Keywords: Gili Iyang Island, Oceanographic Parameters, Coastal TourismABSTRAKPulau Gili Iyang merupakan kawasan dengan potensi dan dapat dimanfaatkan yang dapat menarik minat berkunjung wisatawan domestik maupun wisatawan internasional. Salah satu kawasan wisata yang dapat menjadi daya tarik adalah wisata pantai. Pengembangan kawasan wisata pantai yang baik dapat memberikan dampak positif bagi masyarakat Pulau Gili Iyang. Untuk mengembangakan potensi tersebut dibutuhkan analisa tentang kesesuaian wisata pantai. Sehingga penelitian ini bertujuan untuk mengetahui kondisi parameter oseanografi untuk pengembangan wisata pantai. Penelitian ini menganalisa kualitas air diantaranya suhu, salinitas, DO dan pH, sedangkan analisa kesesuaian wisata pantai diantaranya tipe pantai, kecepatan arus, kedalaman, lebar pantai, material dasar perairan, kemiringan, kecerahan, penutupan lahan perairan, biota berbahaya dan ketersediaan air tawar. Berdasarkan hasil penelitian kualitas perairan di Pulau Gili Iyang Kabupaten Sumenep sesuai dengan standart baku mutu untuk pengembangan wisata pantai. Berdasarkan hasil perhitungan matrik kesesuaian wisata pantai Pulau Gili Iyang memiliki penilaian yang sesuai (S) untuk pengembangan wisata pantai. Kata Kunci : Pulau Gili Iyang, Parameter Oseanografi, Wisata Pantai